Spotlights on certification and farmers' welfare: crossing boundaries in social scientific research. Issue 8 (17th November 2017) - Offermans, Astrid; Glasbergen, Pieter
ABSTRACT: Social scientists have the freedom to adopt different methodological approaches when researching development. This article illustrates how four common social scientific methodologies (positivism, social constructivism, action research, and normative political theory) differently conceptualise the effects of sustainability certification on Indonesian smallholder farmers. It shows that each approach results in different insights, offering a web of information to practitioners. Better understanding the different methodologies may help practitioners to take position in dilemmas, not in a linear process of knowledge accumulation, but in an iterative process of research consultation and practices.